Recycle right: How to decrease recycling contamination with informational point-of-disposal signage - Cakanlar, Aylin; Hunter, Megan; Nenkov, Gergana Y. (Journal of the Academy of Marketing Science, 2025)
Abstract Plastic pollution represents a grand challenge facing society, yet the amount of plastic being recycled is only about 5%. This recycling crisis has intensified with the growing problem of recycling contamination (i.e., incorrect placement of unrecyclable materials in recycling receptacles). This research investigates the potential for informational point-of-disposal recycling signage to decrease recycling contamination. In a longitudinal field study and three experiments, the authors demonstrate that providing schema-congruent prescriptive information (“Recycle these items”) does not reduce recycling contamination and may inadvertently lead to over-recycling. In contrast, the presence of proscriptive information that is moderately incongruent with established schemas (“Do not recycle these items”) prompts more effortful, piecemeal processing. This encourages individuals to integrate the information into their recycling decisions, diminishing their dependence on pre-existing beliefs and expectations regarding recycling and, consequently, lowering contamination rates. Recycling expertise is found to moderate the effects of point-of-disposal recycling signage. By examining such nuanced recycling communication strategies, this research aims to shift the conversation from “recycle more” to “recycle right.”